Evaluation and Community Service Capacity Development through DC Motor System Optimization in the Appropriate Technology Program - Angga Yuda Pratama (Politeknik Perkapalan Negeri Surabaya, 2024)
Optimization plays a critical role in systems related to technology and engineering, particularly in efforts to enhance community empowerment through technology adoption. In this study, optimization is applied to improve the efficiency of community-oriented technology by leveraging optimal control techniques. Specifically, a Linear Quadratic Regulator (LQR) is employed to analyze the step response of the system and its reaction to disturbances, providing precise control for community technology applications such as crafting machines or energy-efficient devices. Before implementing LQR control, simulations using MATLAB Simulink are conducted to determine the optimal gain parameters for the control system. Additionally, Linear Quadratic Tracking (LQT) is utilized to design a closed-loop control scheme aimed at ensuring the system's output signals optimally track the reference signals and effectively reject disturbances. This method provides a robust approach to optimizing devices that directly impact productivity and cost-efficiency in community programs. The proposed solution is formulated by converting the LQT problem into a standard Linear Quadratic Regulation problem, ensuring adaptability for practical implementation. The approach is demonstrated through two simulation examples: a first-order generator and a second-order generator, with the simulation results presented and discussed in detail. These findings highlight the potential of LQR and LQT optimization in improving technological applications in community development programs, contributing to enhanced social and economic outcomes.